Continuous release of O2−/ONOO− in plasma‐exposed HEPES‐buffered saline promotes TRP channel‐mediated uptake of a large cation. Issue 10 (25th May 2020) - Sasaki, Shota; Zheng, Yuexing; Mokudai, Takayuki; Kanetaka, Hiroyasu; Tachikawa, Masanori; Kanzaki, Makoto; Kaneko, Toshiro
Abstract: Although the externally controllable extracellular supply of the short‐lived reactive oxygen and nitrogen species, such as O2 −, NO, and ONOO −, could potentially manipulate cellular functions, their simple administration to cells is likely to be ineffective due to their rapid deactivation. In this study, we found a method of a continuous supply of O2 − /ONOO − over a few minutes, which is triggered by irradiation of a nonequilibrium atmospheric pressure plasma to commonly used organic buffers (e.g., 4‐(2‐hydroxyethyl)‐1‐piperazineethanesulfonic acid, HEPES). In addition, a continuous low‐dose O2 − /ONOO − supply was shown to induce a physiologically relevant Ca 2+ response and subsequently the uptake of a large cation mediated by transient receptor potential channel family member(s). Our results provide a novel approach to the continuous O2 − /ONOO − supply, requiring controllable and mass‐volume treatments. Abstract : A continuous supply of O2 − /ONOO − over a few minutes, which is triggered by irradiation of a nonequilibrium atmospheric pressure plasma to HEPES‐buffered saline, induced a physiologically relevant Ca 2+ response and subsequently the uptake of a large cation mediated by transient receptor potential channel family member(s). Our findings might open up a new way to the continuous supply of short‐lived reactive species.